(untitled) (Journal of Political Sociology, 2025)
In December 2024, we sat down with Ingar Solty to talk about the 2024 US election, Trump’s victory, Harris’ defeat, and the things that we have to expect from the next Trump presidency. In the course of this conversation, we also discussed potential consequences for Europe and the political situation in European states, in particular Germany. As an interplay of various developments on the local, national and international level, Solty describes the ‘Zeitenwende’ as a shift in the geopolitical sphere that results from the re-rise of Trumpism in the United States.